The Prevalence and Quality of Source Attribution in Middle and High School Science Papers. - Michelle Vieyra; Kari Weaver (Issues in Science and Technology Librarianship)
Plagiarism is a commonly cited problem in higher education, especially in scientific writing and assignments for science courses. Students may not intentionally plagiarize, but may instead be confused about what proper source attribution entails. Much of this confusion likely stems from high school, either from lack of or inconsistent instruction across classes. To determine the extent of plagiarism issues in middle and high school student science papers, the authors surveyed student research reports to evaluate their use of in-text and reference page citations. While most of the students had a reference page, fewer than 35% of high school students properly used in-text citations. Furthermore, 12th grade students did not perform any better than 9th grade students in providing proper citations. A survey of college science faculty showed that they do not feel that students are receiving adequate training in source citation in high school. While proper source citation, including the use of in-text citations, is clearly indicated in state education standards, students may not be receiving consistent instruction for a variety of reasons. At a minimum, teachers and officials who supervise student research projects should ensure that students give proper attribution to their sources. This will avoid the development of bad habits that may be troublesome in college. [ABSTRACT FROM AUTHOR]